2020
DOI: 10.5812/ircmj.101688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pilates on Body Composition and Some Biochemical Parameters of Women with Type 2 Diabetes on a Low-Carbohydrate or High-Complex-Carbohydrate Diabetic Diet

Abstract: Background: The prevalence of type 2 diabetes mellitus (T2DM) has increased dramatically in the past 30 years. The World Health Organization has prepared an action plan to stop the increase in diabetes and obesity by 2025. Objectives: This study was conducted to assess the effect of pilates on body composition and some biochemical parameters in women with T2DM on a high-complex-carbohydrate diabetic diet or a low-carbohydrate/high-monounsaturated fatty acids (MUFA) diet. Methods: This experimental study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The risk-of-bias assessment is shown in Figure 2 . All studies were described as randomly generated, while only five of them (Ramezankhany et al, 2011 ; Marinda et al, 2013 ; Zhang and Chen, 2019 ; Batar et al, 2020 ; Cui et al, 2020 ) recorded the methods of randomization in detail. Blinding was described in one study (Jung et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The risk-of-bias assessment is shown in Figure 2 . All studies were described as randomly generated, while only five of them (Ramezankhany et al, 2011 ; Marinda et al, 2013 ; Zhang and Chen, 2019 ; Batar et al, 2020 ; Cui et al, 2020 ) recorded the methods of randomization in detail. Blinding was described in one study (Jung et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diabetic patients from the three studies (Zolfaghari et al, 2015 ; Khormizi and Azarniveh, 2017 ; Zhang and Chen, 2019 ) receiving 8-week interventions, and the HbA1c was pronouncedly higher in the PG than that in the CG after intervention (MD = −0.96%, 95% CI: [−1.06, −0.86]%, P < 0.0001, I 2 = 0%). Six studies (Tunar et al, 2012 ; Yucel and Uysal, 2018 ; Abd EL-Monim et al, 2019 ; Batar et al, 2020 ; Cui et al, 2020 ; Melo et al, 2020 ) reported a 12-week intervention, and we found that diabetes patients receiving 12 weeks of Pilates training showed a greater reduction in HbA1c than those with control conditions (MD = −0.59%, 95% CI: [−1.29, −0.11]%, P = 0.10, I 2 = 92%) ( Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations